2 - Dynamique associative, nouveaux mouvements sociaux et intégration sociopolitique des Haoussa du Cameroun - Ibrahim Mouiche,; Raymond Mbebi Ndema, (African Sociological Review, 2019)
This study concerns the Hausa of southern Cameroon; and for good reason, unlike those in the northern part, notably the Adamawa region where they constitute a digital framework in several departments and therefore eligible for the policy of regional balance, until the political liberalization of the 1990s, the Hausa of southern Cameroon showed very little interest in the public and political sphere, especially since the populations who welcomed them in their localities considered them as “foreigners». The democratization of the 1990s will constitute for them a political opportunity; therefore, they will set up the Ya – kamata and the Bakandamiya, two new social movements (NMS), to try to get out of marginality. This contribution aims to identify this mutation.